LOW TRIIODOTHYRONINE (T3) SYNDROME IN ACUTE HEART FAILURE AND ASSOCIATION WITH SHORT-TERM OUTCOME - G, ASWIN KUMAR; ZACHARIAH, SUE ANN (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objectives: The objectives of the study were to find an association between low T3 syndrome and short-term outcome in patients admitted with acute HF. Heart failure (HF) is a clinical syndrome caused by structural and/or functional cardiac abnormality that causes decreased cardiac output and/or elevated intracardiac pressures. The prognosis of cardiac diseases may be negatively impacted by low-T3 states and was independently linked to higher all-cause mortality in hospitalized HF patients. Methods: 176 patients diagnosed as acute HF fulfilling inclusion criteria were enrolled. Serum fT3, fT4, and thyroid-stimulating hormone were measured. Patients were followed up and length of hospital stay, need for inotropes, mechanical ventilation, and intensive care unit (ICU) facility were compared with thyroid function tests. End points were discharge or death. Data were entered into structured pro forma and analyzed. Results: There was a statistically significant association between need for ICU/high dependency unit (HDU) facility care and T3 status (χ2=27.82; p<0.001). There was a statistically significant association between the need for mechanical ventilation with the levels of T3 (χ2=16.14; p<0.001). There is a statistically significant difference in mean T3 among the patients who expired and patients who were discharged (2.31±0.74 vs. 1.71±0.66; p=0.019). Conclusion: Low T3 correlated with a higher rate of ICU/HDU admissions (53.5% vs. 14.7%, p<0.001) and an increased need for invasive mechanical ventilation (35.6% vs. 9.3%, p<0.001). Low T3 syndrome is frequently found in patients with acute HF and is associated with a poor short-term outcome in terms of need for intensive care and mechanical ventilation.